Antecedents of perceived overqualification: a three-wave study. Issue 4 (10th August 2015) - Guerrero, Laura; Hatala, John-Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the role of job search on perceived overqualification by applying the theory of planned behavior and including financial need and openness to experience as moderators. Design/methodology/approach – Three questionnaires were given at weeks 1, 8 and 12 to 436 practice firm participants. A total of 119 completed all three questionnaires. The authors used partial least squares to analyze the data. Findings – Job search self-efficacy was positively related to job search intentions and to outcome expectations. Job search intentions were positively related to job search intensity. Financial need acted as a moderator of the relationship between job search intensity and perceived overqualification such that for those with high-financial need higher levels of job search intensity resulted in higher perceived overqualification. Research limitations/implications – The authors found little support for the theory of planned behavior in the model. The authors found strong support for the role of job search self-efficacy and job search intentions. The use of a three-wave design resulted in a relatively low sample size and the use of the practice firm reduces the generalizability of the findings. Practical implications – The results suggest that increasing job search self-efficacy and job search intentions while managing the anticipations of job seekers is likely to yield better job search outcomes. Originality/value – This study investigates the role of job search on perceived overqualification. Findings suggest that malleable attitudes during job search such as job search self-efficacy, job search intentions, and anticipations are likely to impact perceived overqualification.